Stavrakakis, Yannis. (2024). Populist Discourse–Recasting Populism research. Routledge, 186 pages - Monteiro, Bianca (Las Torres de Lucca. International Journal of Political Philosophy, 2025)
The review of the book Populist Discourse – Recasting Populism Research, written by Yannis Stavrakakis and launched during the Spring of 2024, provides a comprehensive overview of the arguments raised by the author regarding the recent discussion about populism. Among many qualifications, the book facilitates the debate about populism made by Laclau in On Populist Reason. It shows how it can be applied to research on and about populism to help us have a more rigorous and comprehensive approach to political contexts around the Globe. Stavrakakis continue the critical tradition developed by Laclau and Mouffe, deepening our understanding of populism's discursive dimensions in contemporary politics. In my review, I summarize the book, highlight the positive and negative points of Stavrakakis’ approach, and finalise with a guide to help the reader get the best from the book.